Differences in bipolar disorder type I and type II exposed to childhood trauma: A retrospective cohort study - Hernán F Guillen-Burgos; Juan F Gálvez-Flórez; Sergio Moreno-Lopez; Angela T.H. Kwan; Oscar Gomez; Gerardo González-Haddad; Roger S. McIntyre (Journal of Affective Disorders Reports)
Background: Childhood trauma (CT) exposure is associated with a more pernicious course in bipolar disorder (BD). However, few studies have reported differences between BD I and BD II regarding CT exposure. We explore the differences in the CT trajectories in bipolar disorders. Methods: A retrospective cohort study of individuals with BD (BD I = 73 vs BD II = 73) was carried out. Early age at onset (EAO) and suicide ideation/behavior were used as severity outcomes. Timespan between EAO and treatment was documented and the associations between CT and comorbid alcohol used disorder (AUD), anxiety disorders (AD), and post-traumatic stress disorder (PTSD) were also described. Univariate, bivariate analyses, and a Poisson regression model with bootstrap resampling were used. Results: Higher scores of CT, physical abuse (PA), and sexual abuse (SA) were statistically significant for BD II than BD I (p < 0.001, p = 0.048, p < 0.001, respectively). Early age at onset, suicide ideation/behavior and treatment delay were associated with CT in both BD I and BD II. However, AUD and PTSD showed association with CT only for BD I. Limitations: Sample size, non-comparison control group, and recall bias. Conclusions: There are differences in CT subtype exposure between BD I and BD II with regards to early age onset, suicide ideation/behavior, delayed time to treatment, and comorbid mental disorders. These results claim for early access to strategies such as CT exposure screening in individuals with BD to detect possible pernicious course and improve the quality of life and clinical outcomes.